Absorptive routines and the economic impact of incremental innovations: Developing continuous improvement strategies - Rocío González-Sánchez; Eva Pelechano-Barahona; Sara Alonso-Mu\~noz; Fernando E. García-Mui\~na (Journal of Open Innovation: Technology, Market, and Complexity, 2020)
The important influence that incremental innovation has, both on the organization's results and on the development of disruptive innovations in a synergistic relationship of positive sum, makes it necessary to deepen its study. In the context of absorptive capacity, this paper aims to contribute to the construction of a specific model of routines for more efficient exploitation. The empirical study was carried out in a sample of Spanish manufacturing companies of the PITEC Panel. The results show the superiority of the market as a source of knowledge compared to other sources with more complex knowledge, but not adjusted to the needs of a minor improvement. In addition, the management of external knowledge is a process whose phases are interrelated, so the routines and resources used must contribute to enriching the external knowledge previously acquired and not be redundant. Therefore, that would mean an inefficient allocation of resources for obtaining and exploiting continuous innovation.
Keywords: 650; absorptive capacity; continuous improvement; incremental innovation; profitability; sources of knowledge